The oenological interest of fumaric acid: Stop malolactic fermentation and preserve the freshness of wines - Morata, A. (2019)
ABSTRACT One of the problems related to the increase in average temperatures in the wine-growing regions is the lower accumulation of organic acids in the berries. Wine freshness depends to a great extent on its acidity. Herein, the effectiveness of fumaric acid to inhibit malolactic fermentation or to stop it once initiated is evaluated in order to preserve the malic acid content. Different doses of fumaric acid and SO2 were tested. The ability of these compounds to inhibit bacterial development and stop the malic acid degradation was testedonaredwineofthevarietyVitisviniferaL.cv.Tempranillowhosemalicacidcontentwassetat1.5g/L. The control wine inoculated with 6 log CFU/mL of Oenococcus oeni ﬁnished the malolactic fermentation in 12 days. However, the use of doses equal to or greater than 300mg/L of fumaric acid delayed the onset of malolactic fermentation for more than 50 days with little degradation of malic acid. In addition, fumaric acid proved to be effective in stopping malolactic fermentation already started where the bacterial count was 7 log CFU/mL. Fumaric acid can be considered as a potent inhibitor of malolactic fermentation.